Extraneural metastasis of meningeal haemangiopericytoma to the liver - Yusoff, Ahmad Ramzi; Mokhtar, Suryati; Raman, Krishnan; Singh, Harjit; M Shabery, Noor Afidah (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Yusoff AR, Mokhtar S, Shabery NAM, Raman K, Harjit S. Extraneural metastasis of meningeal haemangiopericytoma to the liver. Turk J Gastroenterol 2019; 30(9): 848-50.